Novel construction of QC-LDPC codes with modified 2-D GRS codes - Ming ZHAO; Xiao-lin ZHANG (Tongxin xuebao, 2015)
The construction method for QC-LDPC (quasi-cyclic low density parity-check) code with modified two-dimensional generalized reed-solomon (2-D GRS) code is proposed using the generator polynomial of GRS code,so thus the constructed code can have better decoding performance.Meanwhile both the quasi dual-diagonal structure and proper weight distributions are considered during the construction.The QC-LDPC codes with different rates are used to compare with the new designed codes.Experimental results show that the proposed method can accelerate the construction and QC-LDPC codes constructed from the proposed method can have better decoding performance while with low encoding complexity.